Enhancing Service Quality Through Organizational Citizenship Behavior - Eman Yassein Ahmed; Amer Abdullatif Kadhum; Noor Bassim Abd; Jafar Ahmad Alserhan (Journal of Techniques, 2023)
This research includes analyzing the impact of organizational citizenship behavior of customer contact employees on the quality of services provided to them. Accordingly, the descriptive analytical approach of the impact of OCB on customer contact personnel on service quality in the municipality was adopted. A random sample was selected consisting of (194) individuals working in the upper, middle, and executive management, administrators, and supervisors of service activities in all departments of the municipality. Which represents part of the research community of (437). The questionnaire was the tool for data collection. Statistical methods such as mean, standard deviation, Spearman’s correlation coefficient, and simple linear regression analysis were used to analyze the data. The results of the quantitative analysis using the value of the correlation coefficient (R2) to test the hypotheses proved that there is a significant effect of the dimensions of organizational citizenship behavior on service quality. The attention to organizational citizenship behavior was at an average level, with weakness in the application of some dimensions of (OCB), which led to a defect in the quality of services provided to citizens. Accordingly, this research suggests motivating employees and encouraging them to perform work with organizational citizenship behaviors and pushing them towards creativity in addition.